Near infrared reflectance spectroscopy (NIRS) analyses of nutrient composition and condensed tannin concentrations in carolina willow (Salix caroliniana). Issue 6 (28th August 2015) - Lavin, Shana R.; Sullivan, Kathleen E.; Wooley, Stuart C.; Stone, Koni; Russell, Scott; Valdes, Eduardo V.
Abstract : Iron overload disorder has been described in a number of zoo‐managed species, and it has been recommended to increase the tannin composition of the diet as a safe way to minimize iron absorption in these iron‐sensitive species. The goal of this study was to examine the potential of near infrared reflectance spectroscopy (NIRS) as a rapid and simple screening tool to assess willow ( Salix caroliniana ) nutrient composition (crude protein: CP; acid detergent fiber: ADF; neutral detergent fiber: NDF; lignin, gross energy: GE) and condensed tannin (CT) concentrations. Calibration equations were developed by regression of the lab values from 2 years using partial least squares on n = 144 NIRS spectra to predict n = 20 independent validation samples. Using the full 2‐year dataset, good prediction statistics were obtained for CP, ADF, NDF, and GE in plant leaves and stems ( r 2 > 0.75). NIRS did not predict lignin concentrations reliably (leaves r 2 = 0.52, stems r 2 = 0.33); however, CTs were predicted moderately well (leaves r 2 = 0.72, stems r 2 = 0.67). These data indicate that NIRS can be used to quantify several key nutrients in willow leaves and stems including concentrations of plant secondary compounds which, depending on the bioactivity of the compound, may be targeted to feed iron‐sensitive browsing animals. Zoo Biol. 34:576–582, 2015. © 2015 Wiley Periodicals, Inc.